Effect of Dy and Nd on ZK10 alloy processed by hot extrusion. Issue 12 (10th September 2017) - Wan, Yingchun; Tang, Bei; Liu, Chuming; Gao, Yonghao; Jiang, Shunong
ABSTRACT: About 0.6%Dy and 0.2%Nd are simultaneously added to ZK10 alloy processed by hot extrusion, and their effects are investigated. Obvious refined grains and weakened texture are observed after addition of Dy and Nd. Significantly improved mechanical performance with increase of 16% in yield strength and of 114% in ductility is obtained compared with ZK10 alloy. The strengthening effect is attributed to the grain refinement and solid solution, and the enhanced ductility results from the refined structure and weakened texture. Better optimization in mechanical performance with enhanced strengthening is generated, compared with the alloy with individual RE element addition. Combined addition of trace Dy and Nd throws light on the wide-range production and application of extruded ZK10 alloy.